STUDI KELAYAKAN AGROINDUSTRI FILLET IKAN NILA (Oreochromis niloticus) DI KABUPATEN MESUJI - Masithoh Priyantini; Neti Yuliana; Sri Hidayati (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2014)
This study was carried out to examine the feasibility of tilapia’s fillet agroindustry in Mesuji District. A series of analysis including the determination of agroindustry location, feasibility analysis in terms of market, technique and technology, management aspects, as well as the financial aspects, and added value analysis has been done. The results showed that this agroindustry was feasible to be developed in Mesuji District based on significant increasing demand for export every year and great potential of tilapia production as raw material of fillet in Mesuji District. Financially, This fillet industry met all the criteria of feasibility such as NPV value was Rp. 1.601.906.357, break even point was reached on the sale of 34.785 kg, with 2,68 year payback period, IRR was greater than the discount factor of 12.75%, that was 39,85%, and the B/C ratio was 1,12. Based on Hayami Methods, processing of tilapia into fillet gave Rp.10.264 of added value. Keywords : agroindustry, tilapia, fillet, feasibility.